The effectiveness of progressive muscle relaxation and interactive guided imagery as a pain-reducing intervention in advanced cancer patients: A multicentre randomised controlled non-pharmacological trial. (February 2019) - De Paolis, Giulia; Naccarato, Alessia; Cibelli, Filomena; D'Alete, Andrea; Mastroianni, Chiara; Surdo, Laura; Casale, Giuseppe; Magnani, Caterina
Abstract: Background and purpose: Interactive guided imagery (IGI) and progressive muscle relaxation (PMR) are complementary therapies with a recognised positive effect on cancer pain relief. This multicentre randomised controlled trial was designed to assess the adjuvant effect of PMR−IGI in alleviating pain in a sample of hospice patients with terminal cancer. Materials and methods: A total of 104 patients were randomised to two groups. Group A patients (n = 53) were administered the Revised Edmonton Symptom Assessment Scale (ESAS-r) and the numerical rating scale (NRS) for pain immediately prior to (T1) and 2 h following an individual PMR−IGI session (T3). Group B patients (n = 51) received usual care and were assessed using the same tools. Acute pain episodes and rescue analgesics over the following 24 h were recorded. Results: The Pain Intensity Difference (NRS at T3-NRS at T1) was 1.83 in group A and 0.55 in group B and was significant in both groups (p < 0.0001). The mean Total Symptom Distress Score declined by 8.83 in group A and by 1.84 in group B.The average difference in the emotional symptoms ESAS-r subscore (anxiety and depression) was 2.93 in group A (p < 0.0001) and 0.07 in group B (p > 0.05). Conclusion: The results of this trial suggest that PMR−IGI may be considered as an effective adjuvant in alleviating pain-related distress in terminal cancer patients. Further studies should be performed to assess the effectiveness of repeated interventions.